My Treatment Approach to Patients With Diffuse Large B-Cell Lymphoma - Armitage, James O. (Mayo Foundation, 2012)
My favored treatment approach for patients with diffuse large B-cell lymphoma continues to evolve. Diffuse large B-cell lymphoma can now be cured in more than 50% of patients. This is a result of improved definitions of the disease, improved diagnostic capabilities, better staging and restaging techniques, a useful prognostic index to guide therapeutic decisions, and the development of increasingly effective therapies. Positron emission tomographic scans have improved the accuracy of both staging and restaging. Findings on a positron emission tomographic scan at the end of therapy are the best predictors of a good treatment outcome. Numerous subtypes of diffuse large B-cell lymphoma have been identified that require specific treatment approaches. For example, plasmablastic lymphoma typically lacks CD20 and does not benefit from treatment with rituximab. Diffuse large B-cell lymphoma originating in specific extranodal sites such as the central nervous system, testes, and skin presents special problems and requires specific treatment approaches. A subgroup of diffuse large B-cell lymphoma with a very high proliferative rate seems to have a poor outcome when treated with CHOP-R and does better with regimens used for patients with Burkitt lymphoma. New insights into the biology of these disorders are likely to further change treatment approaches. Recognition that diffuse large B-cell lymphoma is not one disease, but a variety of clinicopathologic syndromes provides the opportunity to further improve our ability to benefit patients.